2017
DOI: 10.1016/j.jpowsour.2017.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of La1−Sm−Sr CoO3−δ cathode for intermediate temperature solid oxide fuel cells

Abstract: La 1-x Sm x-y Sr y CoO 3-G (LSSC; x=0.475, 0.650, 0.825, y=0.35, 0.40, 0.45) compounds, which have the same compositions as the La 0.7 Sr 0.3 CoO 3-G (LSC) and Sm 0.5 Sr 0.5 CoO 3-G (SSC) mixture (corresponding mole ratio is 3:1, 1:1 and 1:3, respectively), are synthesized through a conventional solid-state reaction and characterized by X-ray diffraction, thermal expansion coefficient, X-ray photoelectron spectrometer and electrical conductivity measurement, as well as the electrochemical impedance spectra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Figure 4a shows the highresolution XPS spectra of Co 2p, which exhibited two main peaks at binding energies of about 781 and 796 eV (assigned to Co 2p 3/2 and Co 2p 1/2 , respectively). While the asymmetric peak shape confirms the presence of multicomponent Co (likely containing Co 2+ , Co 3+ , and Co 4+ ), 45 it appears challenging to reliably assign any specific Co species because of the complexity of the Co XPS data. 46 Nonetheless, it was found that the peak positions for RP-LSCF slightly shifted to more positive binding energy regions compared to SP-LSCF, from which we can conservatively conclude that RP-LSCF has a somewhat lower surface Co oxidation state than SP-LSCF.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Figure 4a shows the highresolution XPS spectra of Co 2p, which exhibited two main peaks at binding energies of about 781 and 796 eV (assigned to Co 2p 3/2 and Co 2p 1/2 , respectively). While the asymmetric peak shape confirms the presence of multicomponent Co (likely containing Co 2+ , Co 3+ , and Co 4+ ), 45 it appears challenging to reliably assign any specific Co species because of the complexity of the Co XPS data. 46 Nonetheless, it was found that the peak positions for RP-LSCF slightly shifted to more positive binding energy regions compared to SP-LSCF, from which we can conservatively conclude that RP-LSCF has a somewhat lower surface Co oxidation state than SP-LSCF.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…The doping of elements with different valence states by the A or B position makes the the material deviate from electrical neutrality. To balance the neutral charge, the B position element changes its valence to compensate for the charge, or the oxygen vacancy is generated to compensate for the charge . Lin et al considered the effect of Sr doping on the capacitance properties of three perovskite materials: LaCoO 3 , LaNiO 3 , and LaMnO 3 . ,, The results show that, with the increase of the Sr doping amount, the oxygen vacancies of the materials increased, and the specific surface areas of the materials increase first and then decrease; however, the lattice distortion of the materials becomes greater.…”
Section: Introductionmentioning
confidence: 99%
“…However, the shift is very slight which is related to the low component of the CoFe alloy and the low sensitivity of the instrument. As shown in Figure S7 b, the peak at 781 and 796 eV can be attributed to Co 2p 3/2 and Co 2p 1/2, and the peak at 781 eV can be indexed to Co 2+ , Co 3+ , and Co 4+ with the decreasing of the binding energy [25, 26] . It can be observed that the peak shifts to low binding energy in LFCO‐750H compared to LFCO‐600H and LFCO‐900 H, which means the increment of the surface Co valence state in LFCO‐750H.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure S7 b, the peak at 781 and 796 eV can be attributed to Co 2p 3/2 and Co 2p 1/2, and the peak at 781 eV can be indexed to Co 2+ ,C o 3+ ,a nd Co 4+ with the decreasing of the binding energy. [25,26] It can be observed that the peak shifts to low binding energy in LFCO-750H compared to LFCO-600H and LFCO-900 H, which means the increment of the surface Co valence state in LFCO-750H. This result shows there is an interaction between the exsolved nanoparticle and the parent perovskite,a nd then caused the electron transfer between the phases.…”
Section: Methodsmentioning
confidence: 87%